Black economy and innovation. A global approximation to the problem - Mould, Joaquín (2003)
The informal economy affects innovation on multiples ways. On one hand,informality has a positive impact over the innovative activity because it  increasescompetition levels and technology diffusion. However, on the other hand, informaleconomy decreases innovation incentives by reducing monopolisticbenefits that motivates innovation. In three economic models at the globallevel, the research found out that informal economy reduces local innovationdevelopment and it decreases the possibility to improve the economic growthin a country. Policy recommendations suggested would be the reduction ofinformal markets, improvements on intellectual property systems and theimplementation of free economics policies that benefit local innovation activity.